KEDUDUKAN SENI DALAM SIWA NATARAJA SEBAGAI INTI PENDIDIKAN KARAKTER (PERSPEKTIF HINDU DI BALI) - I Ketut Sudarsana; I Nengah Juliawan (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Siwa Nataraja as the core of character education is applied directly or indirectly, by giving an important role in building character values. Siwa Nataraja as a sacred figure as the core of character education also serves to instill a spiritual sense of religion, especially Hinduism. The continuity of the learning process with the quantity of material provided and the professionalism of the educators in conveying the meaning and content of the artistic values contained in the narrative of Siwa Nataraja. Siwa Nataraja is an effort to find truth, purity, harmony, through art (satyam, siwam, sundaram). Art in relation to Hinduism in Bali is a worship step to unite with the art creator is Ida Sang Hyang Widhi Wasa.Keywords: Siwa Nataraja, Art, Character Education, Hinduism.